Cellulose-Reinforced Polylactic Acid Composites for Three-Dimensional Printing Using Polyethylene Glycol as an Additive: A Comprehensive Review - Benini, Kelly Cristina Coelho de Carvalho [UNESP] (2023)
Growing concerns about environmental issues and global warming have garnered increased attention in recent decades. Consequently, the use of materials sourced from renewable and biodegradable origins, produced sustainably, has piqued the interest of scientific researchers. Biodegradable and naturally derived polymers, such as cellulose and polylactic acid (PLA), have consistently been the focus of scientific investigation. The objective is to develop novel materials that could potentially replace conventional petroleum-based polymers, offering specific properties tailored for diverse applications while upholding principles of sustainability and technology as well as economic viability. Against this backdrop, the aim of this review is to provide a comprehensive overview of recent advancements in research concerning the use of polylactic acid (PLA) and the incorporation of cellulose as a reinforcing agent within this polymeric matrix, alongside the application of 3D printing technology. Additionally, a pivotal additive in the combination of PLA and cellulose, polyethylene glycol (PEG), is explored. A systematic review of the existing literature related to the combination of these materials (PLA, cellulose, and PEG) and 3D printing was conducted using the Web of Science and Scopus databases. The outcomes of this search are presented through a comparative analysis of diverse studies, encompassing aspects such as the scale and cellulose amount added into the PLA matrix, modifications applied to cellulose surfaces, the incorporation of additives or compatibilizing agents, variations in molecular weight and in the quantity of PEG introduced into the PLA/cellulose (nano)composites, and the resulting impact of these variables on the properties of these materials.